KERJASAMA TIM DALAM PENINGKATAN KUALITAS PELAYANAN DI KANTOR DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Yenny Takdir Takdir (JIA: Jurnal Ilmiah Administrasi, 2020)
Abstract This study aims to find out the Team Cooperation at the Timoreng Panua Village Office in Panca Rijang District, Sidenreng Rappang District, to find out the Quality of Service at the Timoreng Panua Village Office in Panca Rijang District, Sidenreng Rappang District and to find out the Role of Team Cooperation in Improving Service Quality at the Timoreng Panua District Office Panca Rijang, Sidenreng Rappang Regency. The population in this study is the number of family heads, which is 547 people. Sampling uses a random sample technique using the Yount formula by taking 10%, so the sample is 55 people. Data collection techniques used in this study were observation, interviews, questionnaires and literature studies. The collected data is then used in quantitative analysis techniques with frequency tables. The results showed that Team Cooperation at the Timoreng Panua Village Office in Panca Rijang District, Sidenreng Rappang Regency was categorized as good with an average percentage of 66.4%. The indicator that has the highest value is the division of labor of the Timoreng Panua village apparatus in providing services to the community (Cooperation). The Quality of Service Quality in the Office of the Village of Timoreng Panua, Panca Rijang Subdistrict, Sidenreng Rappang Regency is categorized good with an average percentage of 66.28%. The indicator that has the highest value is the ease of information service for the people of Timoreng Panua Village. The Role of Team Cooperation in Improving Service Quality in the Office of the Village of Timoreng Panua, Panca Rijang Subdistrict, Sidenreng Rappang Regency is categorized as good with a percentage of 65%. Keywords: Team Cooperation and Service Quality